Practicality of a Chemistry Science Teaching Module Based on Basic Concepts and Practical Applications for First-Year Biology Education Students - Mohammad Ahdiat; Ila Rosilawati; M. Setyarini; Rabiyatul Adawiyah Siregar (Universitas Lampung, 2026)
Practicality of a Chemistry Science Teaching Module Based on Basic Concepts and Practical Applications for First-Year Biology Education Students, Chemistry learning for biology education students often encounters challenges due to abstract chemical concepts and the limited availability of teaching materials that integrate biological contexts, necessitating practical teaching modules tailored to student characteristics. Objective: This study aims to analyze the practicality level of the Chemistry Science teaching module “Chemistry for Beginners: Basic Concepts and Practical Applications” developed for first-year students of the Biology Education Study Program, FKIP, University of Lampung. Methods: This research employed a quantitative descriptive approach with 80 students from the 2024 cohort as subjects. The instrument was a practicality questionnaire covering nine closed indicators (Likert scale 1-4) and one open-ended suggestion item. Data were analyzed using descriptive percentage statistics and thematic analysis for open-ended suggestions. Results: The results showed that the teaching module achieved a very practical category with an average percentage of 86.4%. The highest indicators were font readability (92.5%) and suitability of material sequence with the lecture contract (91.3%). The three main student suggestions were adding more varied sample questions (45 respondents), explaining formula and symbol notations (28 respondents), and correcting typos (12 respondents). Conclusion: The Chemistry Science teaching module is declared very practical and feasible to use as a supporting teaching material. Improvement recommendations focus on enriching sample questions, compiling a glossary, and enhancing proofreading quality.